(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2026)
We developed and validated a stability-indicating high performance liquid chromatography (HPLC) method for the quantitative determination of vildagliptin in tablet formulations, focusing on its degradation products. The method was developed following the ICH guidelines encompassing precision, accuracy, specificity, linearity, and robustness. Vildagliptin exhibited remarkable linearity (R2 = 0.999) and highly sensitive detection and quantification limits determined at 0.05 and 0.5 μg/ml, respectively. Precision, assessed through intra-day (0.48 %) and inter-day (0.975%) analyses, demonstrated % RSD values within 2.0%, while accuracy was confirmed with average recoveries ranging from 99.54% to 101.5%. Robustness testing revealed acceptable % RSD values when varying mobile phase parameters. Then, stress studies revealed vildagliptin’s susceptibility to acid, base, and oxidative degradation, while maintaining stability under heat and photolytic conditions. Degradation kinetics analysis indicated pseudo-first-order kinetics for degradation in acid, base, and oxidative agents. The half-life (t1/2), calculated using the Arrhenius plot, of the drug indicates the highest stability (t1/2, 990 h) in the heated condition and the lowest stability (t1/2, 115.5 h) in the acidic environment. The method’s application extends to studying vildagliptin stability, suggesting protective measures during storage, particularly in oxidative, acidic, and basic environments, to ensure product stability and efficacy. Dhaka Univ. J. Pharm. Sci. 25(1): 11-19, 2026 (June)